Efficacy and safety of two whole IgG polyvalent antivenoms, refined by caprylic acid fractionation with or without beta-propiolactone, in the treatment of Bothrops asper bites in Colombia. - Otero, R; León, G; Gutiérrez, J; Rojas, G; Toro, M; Barona, J; Rodríguez, V; Díaz, A; Núñez, V; Quintana, J; Ayala, S; Mosquera, D; et al. (2006)
The efficacy and safety of two whole IgG polyvalent antivenoms (A and B) were compared in a randomised, blinded clinical trial in 67 patients systemically envenomed by Bothrops asper in Colombia. Both antivenoms were fractionated by caprylic acid precipitation and had similar neutralising potencies, protein concentrations and aggregate contents. Antivenom B was additionally treated with beta-propiolactone to lower its anticomplementary activity. Analysing all treatment regimens together, there were no significant differences between the two antivenoms (A=34 patients; B=33 patients) in the time taken to reverse venom-induced bleeding and coagulopathy, to restore physiological fibrinogen concentrations and to clear serum venom antigenaemia. Blood coagulability was restored within 6-24 h in 97% of patients, all of whom had normal coagulation and plasma fibrinogen levels 48 h after the start of antivenom treatment. Two patients (3.0%) had recurrent coagulopathy and eight patients suffered recurrence of antigenaemia within 72 h of treatment. None of the dosage regimens of either antivenom used guaranteed resolution of venom-induced coagulopathy within 6 h, nor did they prevent recurrences. A further dose of antivenom at 6 h also did not guarantee resolution of coagulopathy within 12-24 h in all patients. The incidence of early adverse reactions (all mild) was similar for both antivenoms (15% and 24%; P>0.05).